Enhancing specific capacitance and energy density in printed supercapacitors: The role of activated wood carbon and electrolyte dynamics - Hamed Pourkheirollah; Remuel Isaac M. Vitto; Aleksandrs Volperts; Steffen Thrane Vindt; Līga Grīnberga; Gints Kučinskis; Jari Keskinen; Matti Mäntysalo (Carbon Trends)
This study investigates Activated Wood Carbon (AWC) as an electrode material for advancing printed supercapacitors (SCs). AWC, derived from biomass, offers a sustainable alternative to conventional activated carbons. The research highlights the interplay between AWC's structural properties and electrolyte compatibility, addressing challenges in energy storage technologies. Comprehensive analyses, including sorptometry, Raman spectroscopy, X-ray diffraction (XRD), and electrochemical assessments, reveal that AWC's graphitization and structural ordering significantly influence its performance.Printed SCs fabricated with AWC demonstrate superior performance compared to those using benchmark Kuraray YP-80F activated carbon, achieving up to 93 % and 90 % higher specific capacitance and energy density at 1.0 V and 1.2 V, respectively. The enhanced performance is attributed to AWC's increased surface area and pore volume, which provide abundant ion storage sites and improve ion mobility. Furthermore, the porous structure of AWC facilitates better compatibility with KxHyPO4 electrolytes compared to NaCl, with pseudocapacitive effects also contributing to the improved energy storage behavior.This work underscores the potential of biomass-derived carbon materials in creating high-performance, sustainable SCs. Future efforts will focus on optimizing electrode and electrolyte configurations to further enhance device performance, supporting the transition toward renewable energy solutions.